2008
DOI: 10.1002/adsc.200700366
|View full text |Cite
|
Sign up to set email alerts
|

Fast Suzuki–Miyaura Cross‐Coupling Reaction with Hexacationic Triarylphosphine Bn‐Dendriphos as Ligand

Abstract: The application of hexa[(dimethylamino)-methyl]-functionalized triphenylphosphine (1) and its benzylammonium salt, Bn-Dendriphos (2), in the Suzuki-Miyaura cross-coupling of aryl bromides with arylboronic acids is described. The 3,5-bis[(benzyldimethylammonio)methyl] substitution pattern in 2 leads to a rate enhancement compared to both the non-ionic parent compound 1 and triphenylphospine (PPh 3 ) itself. At the same time, the resulting catalytic species are stable towards palladium black formation, even at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…[2,3] Although it is now commonly accepted that strongly basic phosphanes promote the oxidative addition step, [4] the use of bulky phosphanes possibly serves to favour the formation of a monophosphane complex as the most active catalyst as well as to promote reductive elimination. [5,6] Buchwald has shown that high activities can be induced with phosphanes containing the sterically demanding 2,2'-biphenyl motif (Scheme 1). [7][8][9] Abstract: Five conical calix [4]arenes that have a PPh 2 group as the sole functional group anchored at their upper rim were assessed in palladiumcatalysed cross-coupling reactions of phenylboronic acid with aryl halides (dioxane, 100 8C, NaH).…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Although it is now commonly accepted that strongly basic phosphanes promote the oxidative addition step, [4] the use of bulky phosphanes possibly serves to favour the formation of a monophosphane complex as the most active catalyst as well as to promote reductive elimination. [5,6] Buchwald has shown that high activities can be induced with phosphanes containing the sterically demanding 2,2'-biphenyl motif (Scheme 1). [7][8][9] Abstract: Five conical calix [4]arenes that have a PPh 2 group as the sole functional group anchored at their upper rim were assessed in palladiumcatalysed cross-coupling reactions of phenylboronic acid with aryl halides (dioxane, 100 8C, NaH).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in the cross‐coupling of hard organometallic nucleophiles have been accelerated by the design of reactive catalysts with very high turnover frequencies . Published work on the coupling of organolithium reagents offers new insights into the active palladium catalyst.…”
Section: Methodsmentioning
confidence: 97%
“…Recent advancements in the cross-coupling of hard organometallic nucleophiles have been acceleratedb yt he design of reactive catalysts with very high turnover frequencies. [1][2][3][4][5][6] Published work on the coupling of organolithium reagents offers new insights into the active palladium catalyst. For example, high-reactivity catalysts allow for cross-coupling of alkyllithium reagents with aryl bromides and iodides in which lithium-halogen exchange at these positions occursr apidly with high efficiency.T he use of organolithium reagents offer advantages in their ready commercial availability and ease of synthesis, but also in the reduction of (stoichiometric) waste generated because they can be prepared in situ and coupledd irectly.…”
mentioning
confidence: 99%
“…A remarkable enhancement of activity, both in terms of reaction rate as well as in terms of substrate scope, was observed upon the use of 8 b compared to TPP (Table 3, entry 6). [61,62] In further studies, a systematic comparison of the catalytic properties of hexacationic 8 b to those of neutral triarylphosphine ligands that match either the steric or the electronic properties of 8 b, as well as ligands that contain only four (9 b) or two (10 b) cationic groups, was carried out. From these investigations it was concluded that the Coulombic interA C H T U N G T R E N N U N G liA C H T U N G T R E N N U N G gand repulsion that originates from these presence of as much as six permanently charged groups in the ligand structure of 8 b leads to the observed increased activity, rather than the enlarged cone angle or the reduced s-donating strength of 8 b.…”
Section: A C H T U N G T R E N N U N G (Tppts) 3 ]mentioning
confidence: 99%
“…The combination of these ligands with a suitable metal precursor leads to in situ formation of homogeneous catalysts that have found applications in Pd-catalyzed Suzuki-Miyaura reactions as well as in Rh-catalyzed hydroformylation reactions. [49,55,61,62] The electronic properties of all oligocationic ligands in the series have been evaluated through the 1 J P,Se coupling constant of the corresponding phosphine selenides ( Table 2, entries 5-15). [49] Furthermore, for 8 a and 11, the corresponding complexes trans-[RhCl(CO)L 2 ] (L= 8 a, 11) have been synthesized and characterized in terms of the CO stretching frequency (Table 2, entries 28 and 29).…”
Section: Steric and Electronic Properties Of Ionic Phosphine Ligandsmentioning
confidence: 99%